Regulation of Neurotransmitter Vesicles by the Homeodomain Protein UNC-4 and Its Transcriptional Corepressor UNC-37/Groucho inCaenorhabditis elegans Cholinergic Motor Neurons - Lickteig, Kim M. (J Neurosci, 2001)
Motor neuron function depends on neurotransmitter release from synaptic vesicles (SVs). Here we show that the UNC-4 homeoprotein and its transcriptional corepressor protein UNC-37 regulate SV protein levels in specific Caenorhabditis elegans motor neurons. UNC-4 is expressed in four classes (DA, VA, VC, and SAB) of cholinergic motor neurons. Antibody staining reveals that five different vesicular proteins (UNC-17, choline acetyltransferase, Synaptotagmin, Synaptobrevin, and RAB-3) are substantially reduced in unc-4 and unc-37mutants in these cells; nonvesicular neuronal proteins (Syntaxin, UNC-18, and UNC-11) are not affected, however. Ultrastructural analysis of VA motor neurons in the mutant unc-4(e120) confirms that SV number in the presynaptic zone is reduced (∼40%) whereas axonal diameter and synaptic morphology are not visibly altered. Because the UNC-4–UNC-37 complex has been shown to mediate transcriptional repression, we propose that these effects are performed via an intermediate gene. Our results are consistent with a model in which this unc-4 target gene (“gene-x”) functions at a post-transcriptional level as a negative regulator of SV biogenesis or stability. Experiments with a temperature-sensitive unc-4 mutant show that the adult level of SV proteins strictly depends on unc-4 function during a critical period of motor neuron differentiation.unc-4 activity during this sensitive larval stage is also required for the creation of proper synaptic inputs to VA motor neurons. The temporal correlation of these events may mean that a common unc-4-dependent mechanism controls both the specificity of synaptic inputs as well as the strength of synaptic outputs for these motor neurons.